Sosialisasi Peran Penting Komunikasi Dalam Membangun Hubungan Dengan Pelanggan - Ilisa Fajriyati; Mohammad Zainul; Periyadi Periyadi (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
In this increasingly difficult economic situation, there is a lot of competition in various fields, including competition in the business world. Many companies are competing to gain market share, so this spurs companies to strive to continue to progress in improving their business management. In addition, companies are starting to change their view from one that is product or service oriented, to a customer oriented view. One strategy that can be used by companies is to build customer loyalty. Customer loyalty is needed to ensure the company's future. Maintaining customer loyalty is absolutely necessary for a company to survive and be able to compete with other companies.